Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Synthesis of ethyl furfuryl ether (potential biofuel) by etherification of furfuryl alcohol with ethanol over heterogenized reusable H1Cs2PW12O40 catalyst - Mulik, Nagesh L.; Niphadkar, Prashant S.; Bokade, Vijay V. (Research on Chemical Intermediates, 2020)
{Ethyl furfuryl ether (EFE) considered as potential biofuel can replace petroleum diesel up to 100%. EFE also has efficient blending properties with biodiesel to improve its cold flow properties. Herein we demonstrate efficient synthesis of EFE by etherification of renewable furfuryl alcohol (FAlc) with ethanol over heterogenized heteropoly acids. Cs-exchanged heterogenized heteropoly acid (H3-xCsxPW12O40
Keywords: B; etherification; Ethyl furfuryl ether; Furfuryl alcohol; H3-xCsxPW12O40; Heterogenized heteropoly acid; L ration